2023
DOI: 10.3390/ijms241713259
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Toll-like Receptor-4 in Macrophage Imbalance in Lethal COVID-19 Lung Disease, and Its Correlation with Galectin-3

Maria Carmela Pedicillo,
Ilenia Sara De Stefano,
Rosanna Zamparese
et al.

Abstract: To the current data, there have been 6,955,141 COVID-19-related deaths worldwide, reported to WHO. Toll-like receptors (TLRs) implicated in bacterial and virus sensing could be a crosstalk between activation of persistent innate-immune inflammation, and macrophage’s sub-population alterations, implicated in cytokine storm, macrophage over-activation syndrome, unresolved Acute Respiratory Disease Syndrome (ARDS), and death. The aim of this study is to demonstrate the association between Toll-like-receptor-4 (TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Platelets have many TLRs on their cell membrane, including TLR4. Binding of microorganism (virus, bacteria, fungi) to TLR4 induces platelets activation and release of their granule content (many factors involved in different processes) [18] In our previous study, we demonstrated upregulation of TLR4 in lethal SARS-Cov 2 disease [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets have many TLRs on their cell membrane, including TLR4. Binding of microorganism (virus, bacteria, fungi) to TLR4 induces platelets activation and release of their granule content (many factors involved in different processes) [18] In our previous study, we demonstrated upregulation of TLR4 in lethal SARS-Cov 2 disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathological data of selected patients.The group of patients that constituited our study has already been presented in our previous paper, in which we have investigated the role of Toll-Like receptor-4 in macrophage imbalance in lethal COVID 19 lung disease [19]. The characteristics of this group are summarized in the table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Further details were published in our recent publication, in which we studied the involvement of TLR-4 in macrophage imbalances in deadly COVID-19 lung illness [14]. The control cases used in this investigation are surgical lung histological preparations from COVID-19-negative individuals.…”
Section: Clinicopathological Data Of Selected Patientsmentioning
confidence: 99%